Peningkatan Kompetensi Kewirausahaan Masyarakat Melalui Pelatihan dan Pendampingan Usaha di Desa Mekar Jaya, Kecamatan Cilamaya Kulon, Kabupaten Karawang - Asep jamaludin; Yudi firmansyah; Nandang Nandang (Masyarakat Berkarya : Jurnal Pengabdian dan Perubahan Sosial, 2025)
This community service aims to improve the entrepreneurial competence of the Mekar Jaya Village community, Cilamaya Kulon District, Karawang Regency, through training and mentoring for local potential-based businesses. A qualitative approach was used in this activity by involving observation, interviews, and focus group discussions (FGD) with the community and micro-business actors. The program implementation includes three stages: preparation, training, and mentoring. The results of the activity show that the community has great potential in developing local products, but faces obstacles such as lack of knowledge of business management, digital marketing, and product innovation. Through entrepreneurship training, there was an increase in participants' understanding in managing a business, especially in terms of financial planning and marketing strategies. Business mentoring helped participants apply the knowledge they had gained, which was seen from the increase in product quality and market access. The findings also revealed that the success of the activity was greatly influenced by the enthusiasm of the participants and the active involvement of the facilitators. This activity has a positive impact on increasing public awareness of the importance of entrepreneurship as an effort to improve economic welfare. This program is expected to be a model of sustainability that can be applied in other villages by adjusting to their respective local needs and potentials.